2018
DOI: 10.1038/s41467-018-05887-x
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput chromatin accessibility profiling at single-cell resolution

Abstract: Here we develop a high-throughput single-cell ATAC-seq (assay for transposition of accessible chromatin) method to measure physical access to DNA in whole cells. Our approach integrates fluorescence imaging and addressable reagent deposition across a massively parallel (5184) nano-well array, yielding a nearly 20-fold improvement in throughput (up to ~1800 cells/chip, 4–5 h on-chip processing time) and library preparation cost (~81¢ per cell) compared to prior microfluidic implementations. We apply this method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 21 publications
1
84
0
Order By: Relevance
“…We have shown that CUT&Tag provides high-quality single-cell profiles using the ICELL8 nanodispensation system 12 , which allows for imaging prior to reagent addition and PCR. Likewise, CUT&Tag should be suitable for the 10X Genomics encapsulation system 13 by adaptation of their recently announced ATAC-seq single-cell protocol 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that CUT&Tag provides high-quality single-cell profiles using the ICELL8 nanodispensation system 12 , which allows for imaging prior to reagent addition and PCR. Likewise, CUT&Tag should be suitable for the 10X Genomics encapsulation system 13 by adaptation of their recently announced ATAC-seq single-cell protocol 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Although CUT&RUN can generate high-quality data from as few as 100-1000 cells, it must be followed by DNA end polishing and adapter ligation to prepare sequencing libraries, which increases the time, cost and effort of the overall procedure. Moreover, the release of MNase-cleaved fragments into the supernatant with CUT&RUN is not well-suited for application to single-cell platforms 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the number of samples appears more important than read depth, and results using the full set were consistent for a coverage as low as 1-5 million processed reads per sample (see Methods). Although the subsampling results are dataset-specific and difficult to generalize they provide guidelines for the applicability of diffTF and are in line with single-cell ATAC-Seq data analysis that also show robustness for low coverage at the level of genome-wide summary statistics (Mezger et al, 2018) .…”
Section: Case-study I: Quantify Differential Tf Activity In a Large Amentioning
confidence: 67%
“…This is most evident in situations where RNA is prepared from complex mixtures of cells, such as healthy tissues samples and cancer biopsies. Single-cell strategies that can both resolve cell heterogeneity and infer RE activity have been developed, but they still provide a relatively shallow (discontinuous) and noisy view of RE activity per cell (e.g., Buenrostro et al, 2015;Cusanovich et al, 2015;Chen et al, 2018;Cusanovich et al, 2018a;Cusanovich et al, 2018bMezger et al, 2018Kuono et al, 2019). These properties limit the usefulness of single-cell strategies for VEnCode determination, which requires very stringent RE activity criteria, especially for negative RE activity calls.…”
Section: Vencodes Using Single-cell Sequencing Datamentioning
confidence: 99%